Mass and metallicity scaling relations of high-redshift star-forming galaxies selected by GRBs. Issue 3 (25th September 2017) - Arabsalmani, M.; Møller, P.; Perley, D. A.; Freudling, W.; Fynbo, J. P. U.; Le Floc'h, E.; Zwaan, M. A.; Schulze, S.; Tanvir, N. R.; Christensen, L.; Levan, A. J.; Jakobsson, P.; et al.
Abstract: We present a comprehensive study of the relations between gas kinematics, metallicity and stellar mass in a sample of 82 gamma-ray burst (GRB)-selected galaxies using absorption and emission methods. We find the velocity widths of both emission and absorption profiles to be a proxy of stellar mass. We also investigate the velocity–metallicity correlation and its evolution with redshift. Using 33 GRB hosts with measured stellar mass and metallicity, we study the mass–metallicity relation for GRB host galaxies in a stellar mass range of 10 8.2 –10 11.1  M⊙ and a redshift range of z  ∼ 0.3–3.4. The GRB-selected galaxies appear to track the mass–metallicity relation of star-forming galaxies but with an offset of 0.15 towards lower metallicities. This offset is comparable with the average error bar on the metallicity measurements of the GRB sample and also the scatter on the mass–metallicity relation of the general population. It is hard to decide whether this relatively small offset is due to systematic effects or the intrinsic nature of GRB hosts. We also investigate the possibility of using absorption-line metallicity measurements of GRB hosts to study the mass–metallicity relation at high redshifts. Our analysis shows that the metallicity measurements from absorption methods can significantly differ from emission metallicities and assuming identical measurements from the two methods may result in erroneous conclusions.